A Review on Cucumis sativus L. and its Anti-Ulcer Activity - Chattopadhyay, Soumi; Roy, Prodip; Mandal, Diparati (Journal for Research in Applied Sciences and Biotechnology, 2023)
The term "medicinal plant" refers to a plant that has active components with therapeutic properties and is used to treat disease or illness in various medical systems or conventionally. Every continent uses medicinal plants extensively and successfully. Herbal medicine is an extremely well-known and well-documented technique in Asia. Cucumis sativus L. is a well-known medicinal herb having variety of pharmacological activity. In traditional Unani medicine system this plant is use to cure variety of disease, ulcer is one of them. In this article we have discussed about its anti-ulcer potentiality.